PERANCANGAN SISTEM INFORMASI PEMINJAMAN BERKAS REKAM MEDIS PASIEN RAWAT JALAN DI RSAU Dr.M.SALAMUN - Luhukay, Yeska Claudia; Yunengsih, Yuyun; Sufyana, Candra Mecca (JURSIMA, 2022)
Indonesian Air Force Hospital Dr. M. Salamun Air Force Medical Service is a Level II military hospital in Bandung Regency, West Java. The problem encountered with the medical record lending system is that this hospital still uses the manual method of lending medical records, which is only entered in the expedition book, which causes delays in the lending of the medical records used for this by the Officials conduct problem, purpose of research This is done so that the lending information system can be computerized, which can make it easier for medical records unit officials to process loaned medical record files quickly, precisely and accurately. The type of research conducted is qualitative through observation, officer interviews and literature study with software development methods using the waterfall method. The design phase begins with the system requirements analysis phase, after which a flow map is created as the flow of the system process to be created, context diagram, data flow diagram and entity relationship diagram. Implement an information system that supports Microsoft Visual Basic and a Microsoft SQL Server database. The results of the draft lending information system carried out by the officials no longer recorded the lending of medical records in the expedition book. The officers felt supported by the computerized system as the work done was faster